The Political Socialization of Pakistani Youth: A Quantitative Study of Higher Education Institutions in Pakistan - Kataria, Jafar Riaz (South Asian Journal of Religion and Philosophy (SAJRP), 2025)
Educational institutions do not only impart formal education but also serve as agents of political socialization. The present quantitative study examines how higher education institutions in Pakistan contribute to the political socialization of youth and to what extent these institutions encourage political participation and informed citizenship. A survey of 100 university students across three cities (Muzaffarabad, Gujrat, and Lahore) was conducted using a structured questionnaire. Results indicate that the political socialization process among university students is dynamic and multi-faceted, involving various formal and informal agents. Family, peers, media, and educational experiences all significantly shape the political awareness, the attitudes and the behaviour of youth. Notably, while most respondents’ value democratic participation, gaps in political knowledge and trust in media were observed. The findings underscore the need to integrate civic education and open up discourse in university environments to foster informed, active citizens. In the light of these findings, policy measures to strengthen the role of universities regarding political socialization are recommended.